2020
DOI: 10.11604/pamj.2020.36.362.17787
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection in the rural area of Dschang, Cameroon: seroprevalence and associated factors

Abstract: Introduction viral hepatitis B remains a major public health problem around the world, especially in underdeveloped and developing countries. Cameroon shows a grate variability in prevalence of this infection in the country and even within different populations groups. The aim of this study was to determine the prevalence and factors associated with viral hepatitis B infection in the rural area of Dschang. Methods we conducted a cross-sectional community-based study, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Based on ethnicity, the HBV seroprevalence was 36.7% in Cameroonians. Noted that more than 90% of patients were not vaccinated against HBV infection, and this is consistent with a study conducted in Bamenda and Dschang, Northwest and Western regions of Cameroon [28,29]. Thus, the absence of HBV vaccine coverage could explain this high seroprevalence rate found here.…”
Section: Discussionsupporting
confidence: 92%
“…Based on ethnicity, the HBV seroprevalence was 36.7% in Cameroonians. Noted that more than 90% of patients were not vaccinated against HBV infection, and this is consistent with a study conducted in Bamenda and Dschang, Northwest and Western regions of Cameroon [28,29]. Thus, the absence of HBV vaccine coverage could explain this high seroprevalence rate found here.…”
Section: Discussionsupporting
confidence: 92%
“…The statistically significant association between traditional operation or scarification and HBV has also been reported in studies in Africa 21,29 . Traditional operations are common in Africa and involve procedures such as tooth extraction, abortion, injections, incising and draining abscesses, uvulectomy, circumcision, inguinal hernia surgery, non‐invasive cataract luxation and surgery on closed and open fractures 30 .…”
Section: Discussionmentioning
confidence: 71%
“…The statistically significant association between traditional operation or scarification and HBV has also been reported in studies in Africa. 21,29 Traditional operations are common in Africa and involve procedures such as tooth extraction, abortion, injections, incising and draining abscesses, uvulectomy, circumcision, inguinal hernia surgery, non-invasive cataract luxation and surgery on closed and open fractures. 30 In some parts of Africa, cutting out the primary canine tooth buds of infants and toddlers is used as a means of treating or preventing diarrhoea or difficult breastfeeding that is commonly believed to be caused by a worm that lives in the base of the tooth.…”
Section: Ta B L E 3 Prevalence Of Anti-hepatitis C Virus (Hcv) By Age...mentioning
confidence: 99%
“…Indeed, a retrospective study in China showed that HBV infection increases with age, with an adjusted odds ratio of 11.61 for people more than 21 years old. Similarly, a study conducted in Dschang revealed that age, level of education and occupation are all associated with hepatitis B [19]. People in the 17-31 age range were found to be more exposed to HBV, with a prevalence rate of 12.64%.…”
Section: Discussionmentioning
confidence: 90%
“…Patients having tested positive for viral hepatitis more than 6 months ago, and those who stated that they suffered from cirrhosis, fibrosis, steatosis, and liver failure before the study were considered as patients with a chronic liver disease. The minimum sample size (174 subjects) to be used for this study was calculated by the Lorentz formula using the current HBV prevalence (12.75%) in the Adamawa region [19] with a 0.05 degree of precision and 95% confidence level. For more precision, a higher sample size of 225 was considered.…”
Section: Methodsmentioning
confidence: 99%